1990
DOI: 10.1107/s0108270190003134
|View full text |Cite
|
Sign up to set email alerts
|

Structure de Ti6(CH3COO)8(OiPr)8O4

Abstract: Octakis(~-acetato-O, O')-bis(/~-isopropoxy)-hexakis(isopropoxy)-di-/x3-oxo-di-/~-oxohexatitanium, [Ti6(CH3COO)8(O~Pr)804], Mr = 1296.4, triclinic, P1, a = 9.361 (3), b = 11.852 (4), c = 15.791 (5) A, a = 108.54 (3), /3 = 96.54 (3), y = 106.07 (3) °, V = 1556 (2) A3, Z = 1, D,, = 1.32 _ 0-02, Dx = 1.38 Mg m -3, h,(Mo Ka) = 0.71069 A,/~ = 0.798 mm-1, F(000) = 676, T = 298 K, R = 0.059 for 2114 independent reflections. This structure can be described as a hexamer in which Ti atoms, in an octahedral environment, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…Two types of crystals were produced. Yellow blocks were found to be the same as structure (II) (Laaziz et al, 1990) and colourless plates gave spectroscopic data consistent with the structure of (I) (Papiernik et al, 1998), indicating a hexaprismane type complex. We have fully characterized (I) by single-crystal X-ray crystallography.…”
Section: Commentmentioning
confidence: 53%
See 1 more Smart Citation
“…Two types of crystals were produced. Yellow blocks were found to be the same as structure (II) (Laaziz et al, 1990) and colourless plates gave spectroscopic data consistent with the structure of (I) (Papiernik et al, 1998), indicating a hexaprismane type complex. We have fully characterized (I) by single-crystal X-ray crystallography.…”
Section: Commentmentioning
confidence: 53%
“…An examination of solely acetic-acid-modified hexatitanium isopropoxide complexes has produced three of the four possible shapes; a hexaprismane shape for the title compound, (I), has already been predicted by spectroscopic means (Papiernik et al, 1998), and X-ray crystallography has confirmed a rutilane shape for [Ti 6 ( 3 -O) 2 ( 2 -O) 2 ( 2 -OPr i ) 2 (OPr i ) 6 ( 2 -OAc) 8 ], (II) (Laaziz et al, 1990) and a bitricyclane shape for [Ti 6 ( 3 -O) 2 ( 2 -O) 2 ( 2 -OPr i ) 6 -(OPr i ) 6 ( 2 -OAc) 4 ], (III) (Doeuff et al, 1989). Each of the above complexes was prepared using conventional solvent methods.…”
Section: Commentmentioning
confidence: 92%
“…The crystal structures of [6,4] and [6,6] ( R =−H or −CH 3 ) have previously been reported by Laaziz et al ., 44 Boyle et al ., 29 and Papiernik et al ., 30 respectively. In all cases, the bidentate ligands (acetate or formate groups) adopt a bridging geometry and the six‐fold coordination sphere of each Ti(IV) site is satisfied with bridging oxo, carboxylate, and isopropoxy ligands, and terminal isopropoxy groups.…”
Section: Resultsmentioning
confidence: 88%
“…The higher degree of substitution by the bidentate carboxylate ligands forces the structure to become less condensed, since a coordination number larger than six is not possible. A smaller degree of substitution was found in [Ti 6 O 4 (OR) 8 (OOCRЈ) 8 ], [19,49] [Ti 6 O 4 (OR) 12 (OOCRЈ) 4 ], [27] and [Ti 4 O 4 (OR) 4 (OOCRЈ) 4 ]. [50] The titanium atoms are octahedrally coordinated in all derivatives, and the carboxylate ligands are bridging.…”
Section: Introductionmentioning
confidence: 99%